2020
DOI: 10.1002/evan.21857
|View full text |Cite
|
Sign up to set email alerts
|

Mobile containers in human cognitive evolution studies: Understudied and underrepresented

Abstract: Mobile carrying devices—slings, bags, boxes, containers, etc.—are a ubiquitous tool form among recent human communities. So ingrained are they to our present lifeways that the fundamental relationship between mobile containers and foresight is easily overlooked, resulting in their significance in the study of human cognitive development being largely unrecognized. Exactly when this game‐changing innovation appeared and became an essential component of the human toolkit is currently unknown. Taphonomic processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Today, containers are often central to long-term storage of both raw materials, food stuffs, and material culture items—such storage, like transport, reflects thinking of the future. We recently reviewed the physically surviving evidence for containers [71] and found that the oldest examples date back to about 100 000 years ago (Blombos, shell ochre containers [72])—where a ‘roof' in preservation appears to be reached. While many speculate that containers would have been useful at much earlier periods, concrete evidence for them is thus far lacking.…”
Section: Technology and Behaviour Reflecting Foresightmentioning
confidence: 99%
“…Today, containers are often central to long-term storage of both raw materials, food stuffs, and material culture items—such storage, like transport, reflects thinking of the future. We recently reviewed the physically surviving evidence for containers [71] and found that the oldest examples date back to about 100 000 years ago (Blombos, shell ochre containers [72])—where a ‘roof' in preservation appears to be reached. While many speculate that containers would have been useful at much earlier periods, concrete evidence for them is thus far lacking.…”
Section: Technology and Behaviour Reflecting Foresightmentioning
confidence: 99%
“…The origin of container technology was a significant milestone for early humans, 160 but preservation issues challenge our capacity to identify it. Ostrich eggshells, when emptied of their nutritional contents, make excellent storage containers and are known as such ethnographically, and from many LSA archeological contexts of southern Africa.…”
Section: Technologymentioning
confidence: 99%
“…Some recent articles argue that body ornaments found in certain infant burials were likely attached to a fixed object, possibly a blanket, or baby carrier or sling rather than being worn directly as personal ornaments by the young individuals (Henry-Gambier et al ., 2019 , p. 199; Laporte et al ., 2021 ; Laporte & Dupont, 2019 ; Vang Petersen, 2016 ). In fact, recent research suggests that the need for baby carriers may have emerged as soon as hominins became bipedal (Langley & Suddendorf, 2020 ; Suddendorf et al ., 2020 ; Taylor, 2010 ) and that early Homo mothers may have carried their infants to the front of their bodies to increase interaction (Nowell & Kurki, 2020 ). As Vang Petersen argues ( 2016 ), baby carriers were more than likely a common occurrence for prehistoric infants and young children due to the need for parents to remain mobile while taking care of their progeny.…”
Section: Introductionmentioning
confidence: 99%